Government Sector Fraud Analysis From the Fraud Diamond Perspective (Case Study of the Regional Financial Statements of the Southwest Papua Local Government) - Gunawan, Belinda; Nariman, Augustpaosa (Universitas Muhammadiyah Sorong, 2025)
Supreme Audit Board of Republic of Indonesia gave Adverse Opinion for the Financial Statement of Southwest Papua Local Government for the Fiscal Year 2023. Even the Audit Report of the Supreme Audit Board of The Republic of Indonesia on Financial Statement of Southwest Papua Local Government for the Fiscal Year 2023 does not mention